Pseudotumor orbit-bilateral v/s unilateral: a case study of two orbital pseudotumor cases - Nandi, Sunanda; Kuli, Jawahar Jyoti (International Journal of Research in Medical Sciences, 2019)
Orbital pseudotumor is a non-granulomatous inflammation of orbital soft tissue for unknown etiology. In the first case, a 35-year-old female presented with bilateral painless upper eyelid swelling since 3years.No proptosis, no extra ocular movements restriction of both eyes was noted. Best corrected visual acuity both eye: 6/6, N6. USG B-Scan and CECT revealed bilateral lacrimal gland enlargement with bulky muscles and tendons. USG guided FNAC confirmed pseudotumor which showed prompt response to steroids but recurred after 1month of stopping of steroid therapy. In the second Case, a 15year old female presented with unilateral proptosis left eye for 3 months with painful extraocular movements and restricted in all gazes. Best corrected visual acuity in L/E - 6/12, N6, R/E-6/9, N6. USG B-scan and CECT revealed soft tissue lesion encasing Optic nerve. CEMR revealed bulky lacrimal gland, muscles and lesion extending up to orbital apex. Prompt response to steroid with no recurrence till date.